Wildfire effects on soil bacterial community and its potential functions in a permafrost region of Canada - Zhou, Xuan; Sun, Hui; Sietiö, Outi-Maaria; Pumpanen, Jukka; Heinonsalo, Jussi; Köster, Kajar; Berninger, Frank (Applied Soil Ecology, 2020)
Boreal forests in permafrost zone store significant quantities of carbon that are readily threatened by increases in fire frequency and temperature due to climate change. Soil carbon is primarily released by microbial decomposition that is sensitive to environmental conditions. Under increasing disturbances of wildfire, there is a pressing need to understand interactions between wildfires and microbial communities, thereby to predict soil carbon dynamics. Using Illumina MiSeq sequencing of bacterial 16S rDNA and GeoChip 5.0K, we compared bacterial communities and their potential functions at surface and near-surface permafrost layers across a chronosequence (>100 years) of burned forests in a continuous permafrost zone. Postfire soils in the Yukon and the Northwest Territories, Canada, showed a marked increase in active layer thickness. Our results showed that soil bacterial community compositions and potential functions altered in 3-year postfire forest (Fire3) comparing to the unburned forests. The relative abundance of Ktedonobacteria (Chloroflexi) was higher in Fire3 surface soils, while Alphaproteobacteria and Betaproteobacteria (Proteobacteria) were more abundant in unburned ones. Approximately 37% of the variation in community composition can be explained by abiotic variables, whereas only 2% by biotic variables. Potential functional genes, particularly for carbon degradation and anammox, appeared more frequent in Fire3 than in unburned soils. Variations in functional gene pools were mainly driven by environmental factors (39%) and bacterial communities (20%; at phylum level). Unexpectedly, wildfire solely altered bacterial communities and their functional potentials of the surface layers, not the near-permafrost layers. Overall, the response of bacterial community compositions and functions to wildfire and the environment provides insights to re-evaluate the role of bacteria in decomposition. Peer reviewed